Modulation on Optical Limiting and Two-Photon Absorption Behavior of a Molecular Medium by Two-Color Ultrashort Laser Pulses (Journal of Atomic and Molecular Sciences, 2014)
The dynamical behavior of two-color ultrashort laser pulse propagating ina molecular medium 4,4'-bis(di-n-butylamino)stilbene (BDBAS) has been studied byemploying an iterative predictor-corrector finite-difference time domain (FDTD) techniqueto solve the Maxwell-Bloch equations. The results indicate that the spectrumof electric field shows oscillation feature around the two-photon resonant frequencywhen the delay time exists due to the interaction between two sub-pulses. The opticallimiting window turns narrower and the saturation value of output intensity getslarger with the presence of delay time compared with no delay time case. The dynamicalTPA cross section is smaller with the increase of delay time. The studies suggest amethod to modulate the nonlinear optical properties of the medium by controlling thedelay time of the two-color pulse.
Keywords: optical limiting; two-photon absorption; Maxwell-Bloch equations; two-color pulse.